Leo the Great - Leo, I., Papst 400-461 (The early church fathers, 2009)
Leo's life and times. Bishops of Rome as civic leaders -- Barbarian invasions -- Building the church -- The Leonine corpus -- Leo's literary style -- Pastoral caregiver. Fasting and almsgiving -- Condemnation of astrology, and other 'pagan' religious practices -- Importance of the Christian calendar -- Theologian and opponent of heresy. Leo's soteriology and christology -- The struggle against heresy -- Inquiry against the Manichees -- Pelagianism -- Nestorianism -- Eutychianism -- Heir of St Peter. Primacy of the bishop of Rome -- Old Rome versus New Rome : conflict with the church of Constantinople -- Administrator of the wider church. The dispute with Hilary of Arles -- The reception of Leo's letters into canon law -- General introduction to the translations -- Pastoral caregiver. Homily 87 on the September Fast -- Homily 85 on the Feast of St Lawrence -- Homily 27 on the Feast of the Nativity -- Homily 69 on Holy Saturday -- Theologian and opponent of heresy. Homily 16 on the December Fast -- Homily 73 on the Ascension -- Letter 15 to Turibius, Bishop of Astorga -- Letter 28 to Flavian, Bishop of Constantinople -- Letter 124 to the monks of Palestine -- Heir of St Peter. Homily 82B on the Feast of the Apostles -- Homily 84 on the anniversary of Alaric's sack of Rome -- Letter 6 to Anastasius, Metropolitan of Thessalonica -- Homily 4 on the anniversary of Leo's ordination -- Administrator of the wider church. Letter 2 to Septimus, Bishop of Altinum -- Letter 108 to Theodore, Bishop of Fréjus -- Letter 137 to Emperor Marcian -- Letter 167 to Rusticus, Bishop of Narbonne -- Letter 170 to Gennadius, Bishop of Constantinople